IDENTIFIKASI AKTIVITAS ETNOMATEMATIKA PETANI PADI PADA MASYARAKAT JAWA DI DESA SETAIL - Fadlilah, Uun; Trapsilasiswi, Dinawati; Oktavianingtyas, Ervin (Kadikma, 2015)
Abstract. Ethnomathematic is a study done for examines how a group of people in particular culture comprehending, expressing and applying the mathematic concept and use on culture which described mathematically by the researcher. The aim of this research for describing kind of ethnomathematic activity of Javanese in Setail Village. This research is a qualitative ethnographic approach. How to capture the subject of research by the snowball technique, that is by looking one by one the subject prior to the data obtained experiencing saturation point and limited to 7 farmers. The result of this research shown there are mathematic applied on farming done by farmer of Setail Village. They are enumerating, counting, measuring, and designing. Rice farmers of Javanese in Setail Village always use the standard size of land area “seprapat bau” to count and measure in a variety of activities such as determining the amount of fertilizer, medicine, seed number, and number of workers. Counting activities shown when the farmer chopping the frequency of fertilization and seed treatment and plant rice. Designing activities shown when farmers designing farming tool called kerek. Keywords: Ethnomathematics, counting, designing, enumerating, Javanese rice farmers, measuring.